Evidence for genes controlling resistance to Heligmosomoides bakeri on mouse chromosome 1 - Noyes, Harry; Githiori, John; Bradley, Janette E.; Kemp, Steve; Behnke, Jerzy M. (Cambridge University Press, 2015)
Resistance to infections with Heligmosomoides bakeri is associated with a significant quantitative trait locus (QTL–Hbnr1) on mouse chromosome 1 (MMU1). We exploited recombinant mice, with a segment of MMU1 from susceptible C57Bl/10 mice introgressed onto MMU1 in intermediate responder NOD mice (strains 1094 and 6109). BALB/c (intermediate responder) and C57Bl/6 mice (poor responder) were included as control strains and strain 1098 (B10 alleles on MMU3) as NOD controls. BALB/c mice resisted infection rapidly and C57Bl/6 accumulated heavy worm burdens. Fecal egg counts dropped by weeks 10–11 in strain 1098, but strains 1094 and 6109 continued to produce eggs, harbouring more worms when autopsied (day 77). PubMed search identified 3 genes (Ctla4, Cd28, Icos) as associated with ‘Heligmosomoides’ in the B10 insert. Single nucleotide polymorphism (SNP) differences in Ctla4 could be responsible for regulatory changes in gene function, and a SNP within a splice site in Cd28 could have an impact on function, but no polymorphisms with predicted effects on function were found in Icos. Therefore, one or more genes encoded in the B10 insert into NOD mice contribute to the response phenotype, narrowing down the search for genes underlying the H. bakeri resistance QTL, and suggest Cd28 and Ctla4 as candidate genes.